Transformational Change in Delivery at Open Polytechnic, New Zealand - Caroline Seelig (Commonwealth of Learning, 2019)
As long ago as 1992, Greville Rumble was writing about the “competitive vulnerabilities” of single-mode distance teaching institutions [universities]. In the intervening years the challenges he described have only intensified, especially so as advancing information and communication technologies have enabled increasing numbers of campus-based tertiary institutions to enter distance learning, usually targeting the part-time adult learner market that was formerly the preserve of single-mode distance learning providers.